Farmers willingness to pay for water ecosystem services toward forest conservation in North West Selangor Malaysia - Abdulkarim, Buhari; Yacob, Mohd Rusli; Abdullahi, Ahmad Makmom; Radam, Alias (IJECM, 2016)
Forest management practices directly influence the provision of ecosystem services from watershed, and are thus key factors for the development of environmental policy programs such as payment for ecosystem services. This study analyses farmers’ perception and attitude with respect to forest management and conservation at North West Selangor Peat Swamp watershed in Malaysia. This paper attempts to illustrate the use of a structured social psychology methodology, the Theory of Planned Behaviour. Decisions on payment for water irrigation water was elicited among farmers as a function of their attitudes toward forest ecosystem services, Contingent Valuation Method (CVM) was also employed to developed farmers household survey. A descriptive research design was adopted. The survey questionnaire was administered to 380 paddy farmers at North West Selangor irrigation scheme, Malaysia. The result of the Mean WTP was estimated from the dichotomous choice contingent valuation (DC-CVM) was (RM 43.73ha/yr). The expected conservation benefit was estimated to be RM398,773.87/ha/per/yr. The analysis reveals positive attitudes toward ecosystem services.